2009
DOI: 10.1371/journal.ppat.1000321
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in OAS1 Is a Risk Factor for Initial Infection with West Nile Virus in Man

Abstract: West Nile virus (WNV) is a re-emerging pathogen that can cause fatal encephalitis. In mice, susceptibility to WNV has been reported to result from a single point mutation in oas1b, which encodes 2′–5′ oligoadenylate synthetase 1b, a member of the type I interferon-regulated OAS gene family involved in viral RNA degradation. In man, the human ortholog of oas1b appears to be OAS1. The ‘A’ allele at SNP rs10774671 of OAS1 has previously been shown to alter splicing of OAS1 and to be associated with reduced OAS ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(219 citation statements)
references
References 46 publications
9
208
2
Order By: Relevance
“…Infection of mice with WNV led to an increase in the expression of CCR5 and its ligand, which was associated with enhanced migration of leukocytes into the brain and protection of mice against lethal infection [260]. Strong correlation between WNV infection and single nucleotide polymorphisms in IRF3, myxovirus resistance protein 1 and OAS1 was also observed by other studies [259,261]. Similarly, genetic variations within the human OAS1 gene was found to modulate the outcome of infections with TBEV [262], and individuals with major histocompatibility complex B49 on CD8 T cells appeared to be more vulnerable to lethal LACV infections [263].…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fsupporting
confidence: 69%
See 1 more Smart Citation
“…Infection of mice with WNV led to an increase in the expression of CCR5 and its ligand, which was associated with enhanced migration of leukocytes into the brain and protection of mice against lethal infection [260]. Strong correlation between WNV infection and single nucleotide polymorphisms in IRF3, myxovirus resistance protein 1 and OAS1 was also observed by other studies [259,261]. Similarly, genetic variations within the human OAS1 gene was found to modulate the outcome of infections with TBEV [262], and individuals with major histocompatibility complex B49 on CD8 T cells appeared to be more vulnerable to lethal LACV infections [263].…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fsupporting
confidence: 69%
“…Results from previous cohort studies revealed a direct correlation between CCR5 Δ32 homozygosity and symptomatic disease during infections with WNV and TBEV [257,258]. However, the results from recent follow-up studies using larger cohorts failed to show any association between CCR5 deficiency and symptomatic infection with WNV or TBEV [259]. These discrepancies may be explained by differences in study design, cohort size, and the control populations used in these studies.…”
Section: Susceptibility Factors For Arboviral Encephalitis: Lessons Fmentioning
confidence: 79%
“…In another study, an allele of OAS1 ('A' allele at SNP rs10774671) that enhanced mRNA splicing was more common in WNV-infected individuals than in uninfected controls [76]. That study also tested the function of the SNP on viral replication in an ex vivo model using primary human lymphoid tissue and determined that virus replication varied among the donors and was most efficient among individuals who were homozygous for the 'A' allele [80]. In studies of TBE in humans, the same 23 SNPs were analyzed for 142 TBE patients in Russia.…”
Section: Host Determinants Of Flavivirus Encephalitismentioning
confidence: 99%
“…One of the associated polymorphisms, rs10774671, was shown to be associated with reduced OAS activity in peripheral blood mononuclear cells (PBMCs) (Bonnevie-Nielsen et al, 2005). Lim et al (2009) extended these studies by verifying that the OAS1 rs10774671 allele AA genotype was more common in WNV-infected individuals, and that this allele was also associated with increased levels of WNV replication in primary human lymphoid tissue. The authors suggest that induction of OAS1 activity by therapeutic agents may be efficacious in controlling WNV infections.…”
Section: Applied Immunogenomicsmentioning
confidence: 75%